2014
DOI: 10.1002/polb.23472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure on the flow behavior of polybutene

Abstract: The rheology of submicron thick polymer melt is examined under high normal pressure conditions by a recently developed photobleached‐fluorescence imaging velocimetry technique. In particular, the validity and limitation of Reynold equation solution, which suggests a linear through‐thickness velocity profile, is investigated. Polybutene (PB) is sheared between two surfaces in a point contact. The results presented in this work suggest the existence of a critical pressure below which the through‐thickness veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…In the field of tribology, shear localisation has only been directly observed experimentally in viscous model lubricants, such as polybutadiene and polyphenyl ethers (e.g., 5P4E) [196][197][198][199][200][201]. However, it has also been inferred from film thickness measurements in realistic mineral oils [202,203] and there is currently a growing consensus that this phenomenon may also be important for more realistic lubricants under extreme EHL conditions [185].…”
Section: Shear Localisationmentioning
confidence: 96%
“…In the field of tribology, shear localisation has only been directly observed experimentally in viscous model lubricants, such as polybutadiene and polyphenyl ethers (e.g., 5P4E) [196][197][198][199][200][201]. However, it has also been inferred from film thickness measurements in realistic mineral oils [202,203] and there is currently a growing consensus that this phenomenon may also be important for more realistic lubricants under extreme EHL conditions [185].…”
Section: Shear Localisationmentioning
confidence: 96%
“…From these distributions, velocity profiles across EHD films of ca 100 nm thickness were obtained. It was found shown that low MWt polybutenes give Couette shear at low pressure EHD contacts, but form a velocity profile suggestive of plug flow at higher pressures [107]. When a hydrophobic coating was applied to one surface, slip at this surface was observed [108].…”
Section: Probing the Velocity Profile In Ehd Contactmentioning
confidence: 99%
“…Recently a very promising new experimental method for obtaining velocity profiles through EHD films has been described [107]. An EHD contact is established between two glass surfaces using a lubricant containing dissolved fluorescent dye.…”
Section: Probing the Velocity Profile In Ehd Contactmentioning
confidence: 99%
“…6 and 7 can be used to determine the mean temperature of the oil film in the contact for each friction measurement. For tungsten carbide, the product K s qc = 3.3 9 10 8 J 2 K -2 s -1 m -4 , b was 69 lm at a load of 22.7 N and 92 lm at 53.7 N. For most lubricants, K oil was estimated from data in [34] by selecting the nearest fluid type and correcting to the relevant mean contact pressures as suggested in this paper. Atmospheric pressure values for PFPEs were taken from [35] and ionic liquids from [36] and adjusted by assuming a similar conductivity-pressure dependence to other fluid types.…”
Section: Temperature Effectmentioning
confidence: 99%